The Soundscape of Nothing: Raven Chacon’s Silence Against Settler Colonialism (Sound Stage Screen, 2025)
Raven Chacon’s 2022 Pulitzer Prize winning composition Voiceless Mass is only one of many works he has created to engage with cultural and political conceptions of silence. Far from denoting a lack of sound, silence in Chacon’s work often is full of noise that requires different forms of listening. In what follows I argue that Chacon’s use of silence is a direct challenge to the visual and sonic legacy of European landscape art and to a terra nullian ontology that perceives land as empty. In doing so Chacon’s work aligns with a resurgence of Indigenous resistance to settler colonialism and its extractive logics that reached a climax with the resistance to pipeline construction at Standing Rock. By listening to Chacon’s works that engage in silence we can hear a theory of relationship to the land that insists on its sacred fullness of life.